Norma Jeane Baker of Troy : a version of Euripides' Helen - Carson, Anne, 1950- (Oberon Modern Plays, 2019)
"Norma Jeane Baker of Troy is a meditation on the destabilizing and destructive power of beauty, drawing together Helen of Troy and Marilyn Monroe, twin avatars of female fascination separated by millennia but united in mythopoeic force. Norma Jeane Baker was staged in the spring of 2019 at The Shed's Griffin Theater in New York, starring actor Ben Whishaw and soprano Renée Fleming and directed by Katie Mitchell." --